Hubungan Karakteristik Fisik Rumah dengan Kejadian Tuberkulosis Paru di Wilayah Kerja Puskesmas Syamtalira Bayu, Kabupaten Aceh Utara, Indonesia - Khairuman Khairuman; Dian Novita Sari; Erlita Erlita (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2026)
Pulmonary tuberculosis remains a major public health problem in Indonesia, particularly in areas with poor environmental sanitation and unhealthy housing conditions. This study aimed to analyze the association between physical housing characteristics and pulmonary tuberculosis incidence in the working area of Syamtalira Bayu Public Health Center, North Aceh Regency. This analytic observational study used a cross sectional design involving 30 households selected using total sampling technique. Data were collected through interviews and direct environmental observations using structured questionnaires and observation sheets. Variables analyzed included house ventilation and occupancy density. Data were analyzed using Chi square test with 95% confidence level. The results showed that 23.3% of houses had inadequate ventilation and 33.3% had occupancy density that did not meet health standards. Statistical analysis indicated a significant relationship between inadequate ventilation and pulmonary tuberculosis incidence (p=0.021). Houses with inadequate ventilation had a higher risk of tuberculosis transmission compared with houses with adequate ventilation. In conclusion, physical housing conditions play an important role in pulmonary tuberculosis transmission. Improvement of healthy housing conditions is needed as part of community-based tuberculosis prevention programs.